2011
DOI: 10.1159/000325222
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Adversely Affects Quality of Life

Abstract: Background: Chronic liver disease secondary to hepatitis C virus (HCV) infection is a common clinical problem. HCV is likely to adversely affect the quality of life (QoL) of the patient. This effect is said to be disproportionate to the severity of the disease. The aim of our study was to evaluate QoL in HCV-positive patients focusing both on health status and subjective satisfaction. Methods: Twenty-four patients with combined HCV and alcoholic liver disease (ETOH-HCV) were enrolled in the study. We adopted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Many unfounded reasons could be involved: The awareness of having a chronic disease potentially with a poor long-term prognosis, the shame for having been infected, the fear of infecting loved ones, the guilt of having an infection which still today may represent a social stigma as sexually transmitted or substances abuse diseases. Moreover, until a few years ago, the patients were also worried about the limited eradication capacity of interferon based regimens and by their innumerable side effects[25]. The present study confirms that the HRQoL is impaired in HCV population as already observed[8,12-16,25] even in patients with compensated disease.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Many unfounded reasons could be involved: The awareness of having a chronic disease potentially with a poor long-term prognosis, the shame for having been infected, the fear of infecting loved ones, the guilt of having an infection which still today may represent a social stigma as sexually transmitted or substances abuse diseases. Moreover, until a few years ago, the patients were also worried about the limited eradication capacity of interferon based regimens and by their innumerable side effects[25]. The present study confirms that the HRQoL is impaired in HCV population as already observed[8,12-16,25] even in patients with compensated disease.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, until a few years ago, the patients were also worried about the limited eradication capacity of interferon based regimens and by their innumerable side effects[25]. The present study confirms that the HRQoL is impaired in HCV population as already observed[8,12-16,25] even in patients with compensated disease. Fortunately, the emergence of DAAs, with high efficacy rates and tolerability profile, have completely revolutionized the treatment of chronic HCV treatment[13].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…HCV infection is also associated with a wide range of extrahepatic manifestations that include severe neurological disorders including stroke, encephalomyelitis and peripheral neuropathies [24]. Other studies have reported that HCV infection in adults reduced cognitive performance [25,26], psychological functioning [26][27][28] and quality of life [28][29][30][31][32][33]. Although the pathogenesis of all HBV/HCVrelated neuropathies is not fully understood, most evidence points to an upregulated host immune response involving increased production of mono-or polyclonal autoantibodies, immune complexes or cryoglobulins [22,24].…”
Section: Discussionmentioning
confidence: 99%
“…Cirrhosis leads to systemic and metabolic alterations that compromise pulmonary, renal, encephalic, cardiac, and metabolic functions, and complications such as ascites, encephalopathy, jaundice, and sarcopenia, which increase morbidity and mortality and compromise quality of life[ 122 , 123 ].…”
Section: Functional Limitations In Cirrhotic Patientsmentioning
confidence: 99%